Adenosine deaminase mediates endothelial inflammation via an ADA1-CD26 interaction in post-COVID - Kawecka, Ada; Stawarska, Klaudia; Romanowska-Kocejko, Marzena; Żarczyńska-Buchowiecka, Marta; Jędrzejewska, Agata; Braczko, Alicja; Deptuła, Milena; Zawrzykraj, Małgorzata; Król, Oliwia; Frańczak, Marika; Harasim, Gabriela; Pikuła, Michał; et al. (Frontiers in Pharmacology, 2025)
IntroductionAdenosine deaminase (ADA) isoenzymes play a role in microvascular dysfunction following SARS-CoV-2 infection. This study analyzes the mechanisms behind ADA1-dependent endothelial inflammation in post-COVID-19 syndrome. We investigated whether immune cells from post-COVID patients could contribute to the increased total ADA activity. Additionally, we examined ADA’s enzymatic and extra-enzymatic activities in human primary lung microvascular endothelial cells (HULECs) stimulated with post-COVID patients’ serum.Methods and resultsTreatment of HULECs with sera from post-COVID patients resulted in elevated levels of the ADA1 isoenzyme and the ADA1-anchoring protein, CD26. This increase correlated with enhanced adhesion of THP-1 monocytes/macrophages to HULECs. Inhibiting the ADA1-CD26 interaction with glycoprotein-120 prevented the rise in cell-surface ADA levels in HULECs and reduced the adhesion of THP-1 cells to the endothelium. A similar effect was observed when HULECs were pre-incubated with the SARS-CoV-2 spike protein, which co-localized with CD26 in activated HULECs.ConclusionsWe propose that ADA1 promotes vascular inflammation in post-COVID-19 syndrome through both canonical and non-canonical mechanisms. On one hand, its increased enzymatic activity can suppress adenosine-dependent pathways. On the other hand, ADA1 may function as an adhesion molecule facilitating interactions between immune cells and the endothelium via ADA1-CD26 complexes.